Anatomical investigation of elongated styloid processes (Eagle syndrome) with micro-CT analysis and clinical review - Anders, Joseph X.; Srinivasan, William; Minett, Maggie M.; Bare, Susan P.; Akhter, Mohammed P.; Snow, Ethan L. (Translational research in anatomy, 2025)
Eagle syndrome is a rare disease that causes elongation (>30 mm) of the temporal styloid process (SP) through osteogenesis (Type I) or ossification of the stylohyoid ligament (SHL) (Type II). Eagle syndrome implicates the styloid apparatus and can cause difficulty with swallowing, pain with neck movement, dissection of the internal carotid artery, and stroke. Reports investigating the Eagle syndrome gross anatomy and SP microstructure are scarce. This study seeks to investigate a case of Eagle syndrome SPs in a human cadaver with gross and micro-CT analysis and discuss its clinical significance. The case was discovered during routine academic dissection of an adult male human cadaver. The styloid apparatus was examined bilaterally for any non-typical morphologies. The SPs were stripped of extraneous tissue and photographed. Linear and angular dimensions of the SPs were measured, and micro-CT analysis was performed on a section of the right SP. A comprehensive review of Eagle syndrome etiology, epidemiology, symptomology, diagnostic parameters, subtype descriptions, and treatment was compiled from current literature as a basis for clinical discussion. The long axes of the right and left SPs measured 41.4 mm and 33.0 mm, respectively, and the proximal, middle, and distal SP diameters averaged 4.2 mm, 3.5 mm, and 1.7 mm, respectively. Both SPs exhibited a mid-shaft tubercle, after which they decreased diameter by over 25% within 2 mm distance, increased angle of descent by more than 20.0° in the sagittal plane and exhibited noticeably different surface characteristics. Micro-CT analysis revealed relatively consistent trabeculae and cortical structure throughout the SP. Clinical understanding of SP hyperplasia vs. SHL metaplasia as it applies to Eagle syndrome etiology and subsequent implications to the styloid apparatus is important for Eagle syndrome diagnosis, treatment, and patient outcomes. As Eagle syndrome can present with broad symptomology, this report may benefit primary care physicians, dentists, neurologists, radiologists, otorhinolaryngologists, and other medical professionals with information that can be used to improve diagnostic testing and treatment approaches in patients with Eagle syndrome. •Structural and functional outline of the styloid apparatus and stylohyoid chain/complex.•Summary of stylohyoid chain development.•Review of Eagle syndrome etiology, epidemiology, symptomatology, diagnosis, subtype descriptions, and treatment.•Gross cadaveric imaging and analysis of elongated styloid processes (Eagle syndrome).•Micro-CT analysis of an elongated styloid process (Eagle syndrome).